Depth encoded input polarisation independent swept source cross-polarised optical coherence tomography probe - Blessing, Katharina; Schirmer, Judith; Parmar, Asha; Singh, Kanwarpal (Journal of Physics D: Applied Physics, 2021)
Within the last decades, several studies have been published that prove the benefit of polarisation sensitive optical coherence (psOCT) tomography for the field of biomedical diagnostics. However, polarisation sensitive imaging typically requires careful control of the polarisation state of the input illumination, which leads to bulky and delicate systems. While psOCT provides quantitative information, it is mostly sufficient to analyse the images qualitatively in the field of biomedical diagnostics. Therefore, a reduced form of this technique, cross-polarised optical coherence tomography (cpOCT), moves into the focus of interest that serves to visualise the birefringence properties of a sample. Despite the low requirements for the illumination's polarisation, most of the proposed systems still include complex illumination control mechanisms. Here, we propose a common path probe based endoscopic system with an lateral resolution of 30 mu m and a sensitivity of 103 dB comprising a commercially available swept-source OCT system and a free-space module which does not require any polarisation controlling elements. A Faraday mirror substitutes the complex polarisation control apparatus. We demonstrate the independence of the approach from the polarisation state of the light source by monitoring the illumination power in the orthogonal channels while varying the source polarisation. Furthermore, we validate the ability of the system to reveal the birefringence properties of different samples, starting from a quarter-wave plate, since its properties are fully characterised. Additionally, we present imaging results from several tissues to demonstrate its feasibility for the field of biomedical diagnostics.
CRIS-Team WoS Importer:2021-06-04